Influence gaining commitment, getting results - Scharlatt, Harold; Smith, Roland (Center for Creative Leadership, 2011)
If you've got an idea you want to sell, you need to do two things: scan your environment and use effective tactics. This book explains how to scan your environment and provides a collection of tactics you can use to sell your idea. Using this systematic approach will make you more likely to accomplish your objective--solving a problem or making an improvement for the benefit of individuals, groups, and the organization as a whole.
Includes bibliographical references
Keywords: Influence (Psychology); Negotiation in business; Leadership; Influence (Psychologie); Négociations (Affaires); BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; BUSINESS & ECONOMICS; Workplace Culture